Nursultan Nazarbayev — leader and diplomat - Yedgina, G.T.; Taam, Khaled Abou (Publ.KarSU, 2018)
The article examines Kazakhstani modernization that assumed the creation of a national state, the formation of a political nation, the creation of a modern economy and political system. In a historically polyethnic country, the solution of this problem was particularly complex, requiring exclusive approaches and reliance on the political technologies that contributed to the peaceful and evolutionary transition of Kazakhstan society to a qualitatively new state. The article describes the features of the political style of N.A. Nazarbayev, as well as the key features of Kazakhstan's policy. A balanced multi-vector foreign policy that allows building mutually beneficial relations with all major «global players», strengthening national sovereignty and independence in foreign policy, is of great importance among Kazakhstan's political priorities. It is concluded that the time of Nursultan Nazarbayev's presidency is unequivocally highly appreciated. He led the country with a complex interethnic relations that arose as a result of the collapse of a single state. Given the complexity of this potentially explosive problem, Nursultan Nazarbayev successfully created a fairly harmonious relationship between the main ethnic groups living in the country.
Нұрсұлтан Назарбаев — көшбасшы жəне дипломат
Нурсултан Назарбаев — лидер и дипломат
Keywords: Republic of Kazakhstan; President; history; government; relationship; world; policy; foreign